Alat Pengukur Ketinggian Air Pada Landasan Pacu Pesawat Dengan Metode Image Processing - ivan Finiel Hotmartua Bagariang; Hendrick Hendrick (Elektron : Jurnal Ilmiah, 2021)
An aircraft accident are caused by several factors, one of which is the weather. High rainfall causes the runway to become slippery and wet. This will cause hydroplaning events on the plane. Hyproplaning is a skidding event caused by puddles of water on the runway. The maximum height of puddles on the runway is 3 mm. Currently, to measure the water level is still done in a conventional way and there is no sensor capable of measuring the water level in mm. To prevent accidents due to hydroplaning, a measuring device is needed that can monitor the water level in millimeters and has a long size range and is calibrated on the runway. This water level meter is made using a raspberry Pi 3 B+ miniPC. The stages in making this tool include hardware design and software design. Measurements were carried out using the image processing method with a Raspberry Pi camera and an optical liquid water sensor. The results of the measurements are displayed on the monitor screen with the VNC Viewer software. The measurement results using an optical liquid water level sensor are accurate with a relative error of 0% in each measurement, namely at 1 mm, 2 mm and 3 mm. For measurements using the image processing method, the average error generated is 2.3% at a height of 1 mm, 6.9% at a height of 2 mm, 3.3% at a height of 3 mm, 0.9% at a height of 4 mm and 0 .24% at 5 mm height.